Ability profile of the elite volleyball player - Kioumourtzoglou, E.; Michalopoulou, M.; Tzetzis, G.; Kourtessis, T. (Perceptual and Motor Skills, 2000)
The aim of this study was to examine the cognitive, motor, and perceptual abilities of elite volleyball players. These abilities were considered responsible for high quality performance by expert athletes. The elite group was formed with 12 members of the Greek Junior National Volleyball team. A group of 18 physical education students were the novice athletes. The measured abilities were selected by expert volleyball coaches as those most important for an elite athlete. Analysis showed differences between the abilities of the two groups of athletes were significant. An ability profile for the elite volleyball player can be formed.